Effect of carbon steel metallurgy on the inhibition of carbon dioxide corrosion by film forming inhibitors - Bailey, Stuart; John, Doug; Kinsella, Brian; De Marco, Roland (Australian Corrosion Association, 2009)
The internal corrosion of carbon steel pipelines by carbonic acid is commonly controlled using film forming corrosion inhibitors. Generic filming forming corrosion inhibitors are surfactant molecules that adsorb at the corroding steel surface to form a barrier against the corrosive aqueous compontents. These surfactant molecules form distinct adsorbed surface geometries of spheres, rods and bilayers where the packing of these surface geometries may be influenced by the metallurgy of the steel. This paper explores the effect of several different metallurgies (Grade 1020, API 5L X65 and API 5L X60) on the efficacy of generic and commerical corrosion inhibitor compounds. The study investigated six inhibitors, four analytical grade single component pure compounds (cetyl pyridinium chloride (CPC), dodecyl pyridinium chloride (DPC), 1-hydroxyethyl-2-oleic imidazoline hydroclhoride (OHEI) and cetyl dimethyl benzyl ammonium chloride (CDMBAC)), and two commerical corrosion inhibitor formulations denoted as CI(A) and CI(B).